The Implementation of Educational Games as a Digital Learning Culture in Elementary School Learning - Faridahtul Jannah; Shofia Hattarina; Dyah Ariyanti (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Learning with technology content, including computer science or informatics, is a very crucial topic at this time. Unfortunately, there are still many schools that have not adapted to this digitalization culture. There are many factors behind schools not starting a digitalization culture, such as facilities and infrastructure and human resources that are not ready yet. One school that has not implemented digitalization in learning is SDN Kedungdalem. This school still does not have digital-based learning media, most of the learning activities are carried out using books and worksheets. This situation makes students not excited about learning because it is not interesting for students. The aim of this research is to analyze the description of the results of students' academic responses to ICT learning and educational games that have been given. The research method used in this activity is a qualitative approach with rural operations. The subjects of this research were 5th grade students at SDN Kedungdalem. The research results showed that students really liked the educational games provided because the games were funny, exciting and fun.